Overall survival in patients with BRAF-mutant melanoma receiving encorafenib plus binimetinib versus vemurafenib or encorafenib (COLUMBUS): a multicentre, open-label, randomised, phase 3 trial. Issue 10 (October 2018) - Dummer, Reinhard; Ascierto, Paolo A; Gogas, Helen J; Arance, Ana; Mandala, Mario; Liszkay, Gabriella; Garbe, Claus; Schadendorf, Dirk; Krajsova, Ivana; Gutzmer, Ralf; Chiarion Sileni, Vanna; Dutriaux, Caroline; et al.
Summary: Background: Encorafenib plus binimetinib and encorafenib alone improved progression-free survival compared with vemurafenib in patients with BRAF V600 -mutant melanoma in the COLUMBUS trial. Here, we report the results of the secondary endpoint of overall survival. Methods: COLUMBUS was a two-part, randomised, open-label, phase 3 study done at 162 hospitals in 28 countries. Eligible patients were aged at least 18 years with histologically confirmed, locally advanced, unresectable, or metastatic cutaneous melanoma, or unknown primary melanoma, BRAF V600E or BRAF V600K mutation, an Eastern Cooperative Oncology Group (ECOG) performance status of 0 or 1, and were treatment naive or had progressed on or after first-line immunotherapy. In part 1 of the study, patients were randomly assigned (1:1:1) by use of interactive response technology to receive oral encorafenib 450 mg once daily plus oral binimetinib 45 mg twice daily (encorafenib plus binimetinib group), oral encorafenib 300 mg once daily (encorafenib group), or oral vemurafenib 960 mg twice daily (vemurafenib group). Randomisation was stratified by the American Joint Committee on Cancer stage, ECOG performance status, and BRAF mutation status. The primary outcome of the trial, progression-free survival with encorafenib plus binimetinib versus vemurafenib, was reported previously. Here we present the prespecified interim overall survival analysis. Efficacy analyses were by intent to treat. Safety was analysed in patients who received at least one dose of study drug. Part 2 of the study was initiated at the request of the US Food and Drug Administration to better understand the contribution of binimetinib to the combination therapy by comparing encorafenib 300 mg once daily plus binimetinib 45 mg twice daily with encorafenib 300 mg once daily alone. Results of part 2 will be published separately. This trial is ongoing and is registered withClinicalTrials.gov, numberNCT01909453, and EudraCT, number 2013-001176-38. Findings: Between Dec 30, 2013, and April 10, 2015, 577 of 1345 screened patients were randomly assigned to receive encorafenib plus binimetinib (n=192), encorafenib (n=194), or vemurafenib (n=191). Median follow-up for overall survival was 36·8 months (95% CI 35·9–37·5). Median overall survival was 33·6 months (95% CI 24·4–39·2) with encorafenib plus binimetinib and 16·9 months (14·0–24·5) with vemurafenib (hazard ratio 0·61 [95% CI 0·47–0·79]; two-sided p<0·0001). The most common grade 3 or 4 adverse events did not change substantially from the first report; those seen in more than 5% of patients treated with encorafenib plus binimetinib were increased γ-glutamyltransferase (18 [9%] of 192 patients), increased blood creatine phosphokinase (14 [7%]), and hypertension (12 [6%]); those seen with encorafenib alone were palmar-plantar erythrodysaesthesia syndrome (26 [14%] of 192 patients), myalgia (19 [10%]), and arthralgia (18 [9%]); and with vemurafenib the most common grade 3 or 4 adverse event was arthralgia (11 [6%] of 186 patients). One death in the combination treatment group was considered by the investigator to be possibly related to treatment. Interpretation: The combination of encorafenib plus binimetinib provided clinically meaningful efficacy with good tolerability as shown by improvements in both progression-free survival and overall survival compared with vemurafenib. These data suggest that the combination of encorafenib plus binimetinib is likely to become an important therapeutic option in patients with BRAF V600 -mutant melanoma. Funding: Array BioPharma, Novartis.